Asphalt solid phase composition for coating, modified asphalt coated natural graphite negative electrode material and preparation thereof and lithium ion battery

By adding a modification additive to the asphalt solid phase composition, the wetting property of asphalt on graphite is improved, and a uniform and dense amorphous carbon cladding is formed, which solves the problem that the asphalt on graphite impregnation process in the prior art is not paid attention to, and the electrochemical performance of the negative electrode material is significantly improved.

CN119320567BActive Publication Date: 2025-03-07MINMETALS EXPLORATION & DEVELOPMENT CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411859468.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-07
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

In the preparation process of modified asphalt coated natural graphite negative electrode materials, the prior art failed to effectively pay attention to the wetting process of asphalt on graphite, resulting in poor material performance.

Method used

The asphalt solid phase composition for coating is adopted, including coated asphalt and a modification additive. By using a saturated long-chain component, low-molecular wax component and components containing modification groups in the modification additive, the softening point and viscosity of the asphalt are reduced, the wettability of the asphalt on graphite is enhanced, and a uniform and dense amorphous carbon coating is formed.

Benefits of technology

The electrochemical performance of the negative electrode material is significantly improved, including the first week Coulomb efficiency and long cycle performance, reduces the specific surface area and AC impedance, and has a simple process and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320567B_ABST
    Figure CN119320567B_ABST
Patent Text Reader

Abstract

The present invention provides a coating asphalt solid phase composition, a modified asphalt coated natural graphite negative electrode material and its preparation and a lithium ion battery, wherein the coating asphalt solid phase composition is used to form an amorphous carbon coating layer coated on the surface of natural graphite, including coating asphalt and a modification aid, wherein the mass ratio of natural graphite, coating asphalt and modification aid is 1000:45-80:3-12; the modification aid includes a saturated long chain component, a low molecular wax component and a component containing a modification group in a mass ratio of 2-10:0.5-5:0.5-7. The present invention reduces the softening point and viscosity of asphalt, improves the wettability and contact of asphalt to graphite, improves the density and uniformity of the coating layer, and thus improves the electrochemical performance of the natural graphite negative electrode material by adding a modification aid. The negative electrode material of the present invention has a higher first-week coulomb efficiency, better cycle performance, lower impedance and lower specific surface area under the condition of low asphalt addition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a coating asphalt solid phase composition, a modified asphalt coated natural graphite negative electrode material and its preparation and a lithium ion battery, belonging to the field of material technology, especially the field of electrode material technology. Background Art

[0002] Lithium-ion secondary batteries are widely used in smart phones, laptops, electric vehicles, energy storage systems and other fields due to their significant advantages such as high energy density, long cycle life, low self-discharge rate and environmental protection. The storage and release of electrical energy is achieved by the reversible embedding and extraction of lithium ions between positive and negative electrode materials. The core components of lithium-ion secondary batteries include positive electrode materials, negative electrode materials, separators and electrolytes. Among them, the negative electrode material is the carrier of lithium ions during the charging process of the battery. The performance of the negative electrode material directly affects the key indicators of lithium-ion batteries such as energy density, cycle life, and safety performance. Negative electrode materials with good cycle stability can extend the service life of the battery.

[0003] Lithium-ion battery negative electrode material is one of the most important applications of graphite materials. Among them, battery manufacturers use either natural graphite or artificial graphite as negative electrode material for lithium-ion batteries. Artificial graphite faces the bottleneck of development due to the processing of ultra-high energy consumption and ultra-high carbon emission raw materials from fossil energy sources; in contrast, natural graphite has significant resource advantages. However, although the natural graphite negative electrode material has a high gram capacity, it has defects such as bulk / surface defects, large expansion effect, anisotropy, and poor compatibility with electrolytes, which lead to deviations in its cycle stability. In this regard, the most mature negative electrode material production process is to use common asphalt coating materials and spherical graphite solid-solid mixing and carbonization treatment under a protective atmosphere. This generation process can significantly improve the various electrochemical properties of natural graphite negative electrode materials by forming an amorphous carbon layer on the graphite surface, repairing graphite surface defects, and reducing the co-embedding phenomenon of lithium ions and electrolyte molecules. In addition to the performance of the spherical graphite itself, the performance of the coating material is the decisive factor for the negative electrode material.

[0004] For example, CN113991076A uses polyurethane and ZnO to dope and modify asphalt, densifying the carbonized layer by increasing the softening point of asphalt, reducing the content of light components in the asphalt matrix, and enhancing the stability of asphalt. CN115093874A performs steam stripping on oxidized asphalt to obtain low quinoline insolubles and high softening point petroleum-based coated asphalt.

[0005] It can be seen that the current existing technology for modification of coated asphalt mainly focuses on increasing the coking value and reducing the content of light components in asphalt. The modification process mostly involves cross-linking reactions, pre-oxidation, dissolution and extraction of components, etc., and the preparation process is relatively complicated. However, few researchers pay attention to the wetting process of asphalt on graphite during the carbonization process, and modify the asphalt according to the wetting process to obtain negative electrode materials with better performance.

[0006] Therefore, providing a new type of asphalt solid phase composition for coating, modified asphalt coated natural graphite negative electrode material and its preparation and lithium ion battery has become a technical problem that needs to be solved urgently in this field. Summary of the invention

[0007] In order to solve the above shortcomings and deficiencies, the purpose of the present invention is to provide a coating asphalt solid phase composition, a modified asphalt coated natural graphite negative electrode material and its preparation and a lithium ion battery. The present invention uses a modification aid when preparing the modified asphalt coated natural graphite negative electrode material, which can improve its electrochemical performance and improve its various electrochemical performances in a balanced manner.

[0008] In order to achieve the above objectives, on the one hand, the present invention provides a coating asphalt solid phase composition for forming an amorphous carbon coating layer coated on the surface of natural graphite, wherein the coating asphalt solid phase composition comprises coating asphalt and a modifying agent, wherein the mass ratio of natural graphite, coating asphalt and modifying agent is 1000:45-80:3-12; the modifying agent comprises a saturated long-chain component, a low-molecular wax component and a component containing a modifying group in a mass ratio of 2-10:0.5-5:0.5-7.

[0009] As a specific embodiment of the above-mentioned asphalt solid phase composition for coating of the present invention, the mass ratio of natural graphite, coating asphalt and modification auxiliary agent is 1000:45-60:4.5-9.

[0010] As a specific embodiment of the above-mentioned asphalt solid phase composition for coating of the present invention, the mass ratio of the saturated long-chain component, the low-molecular wax component and the component containing the modified group is 3-8:1-4:1-6.

[0011] As a specific embodiment of the above-mentioned asphalt solid phase composition for coating of the present invention, the modification aid is a powder, and the median particle size D50 is 3-20μm, preferably 5-10μm. The median particle size of the modification aid is highly correlated with the uniformity of the mixture. Obviously, the smaller the median particle size, the more uniform the modification aid in the mixture. However, since the modification aid is mostly an organic component or carries a special group, a too low median particle size will lead to serious static electricity on the surface of the modification aid powder, which is not conducive to the transportation and processing of the powder.

[0012] As a specific embodiment of the above-mentioned asphalt solid phase composition for coating of the present invention, the carbon number of the saturated long-chain component is 15-200.

[0013] As a specific embodiment of the above-mentioned asphalt solid phase composition for coating of the present invention, the saturated long-chain component includes one or a combination of several of stearic acid, stearic acid amide, eicosanoic acid and Sasobit.

[0014] The saturated long-chain components used in the present invention are saturated long-chain aliphatic compounds or their modified products, etc. These substances are easily soluble in asphalt, with a melting point between 80-115°C, can enhance the fluidity of asphalt, and improve the melting drop characteristics of asphalt; and the substances are preferentially gasified and decomposed during the asphalt carbonization process, and there is no residue after carbonization, so they are safe and non-toxic, and are suitable as the main agent in the modification auxiliary agent.

[0015] As a specific embodiment of the above-mentioned asphalt solid phase composition for coating of the present invention, the molecular weight of the low molecular wax component ranges from 100 to 5000.

[0016] As a specific embodiment of the above-mentioned asphalt solid phase composition for coating of the present invention, the low molecular weight wax component includes one or a combination of several of synthetic Fischer-Tropsch wax, polyethylene wax, Honeywell wax powder, microcrystalline wax and lignite wax.

[0017] The low molecular wax component used in the present invention has good compatibility with asphalt and can significantly reduce the viscosity of asphalt at high temperature. However, since it is a light component, excessive addition may be detrimental to the performance of the negative electrode material. Among them, polyethylene wax is the most common. Polyethylene waxes from different sources have different synthesis pathways, components, and drop melting points, and have different modification effects on asphalt. Those skilled in the art can reasonably select polyethylene waxes from corresponding sources according to the desired modification effect. For example, in some specific embodiments of the present invention, the polyethylene wax may be BASF polyethylene wax, etc.

[0018] As a specific embodiment of the above-mentioned asphalt solid phase composition for coating of the present invention, the modified group includes one or a combination of amino group, sulfonic acid group, maleic anhydride group and carboxyl group.

[0019] As a specific embodiment of the above-mentioned asphalt solid phase composition for coating of the present invention, the component containing the modified group includes one or a combination of p-aminobenzenesulfonic acid, maleic anhydride grafted polyethylene wax, benzenesulfonic anhydride and sulfobenzoic acid.

[0020] The components containing modified groups used in the present invention all have high melting points and high decomposition points, and contact and react with the components in the asphalt to ensure that they can play a role in surface modification during the asphalt softening process. Among them, p-aminobenzenesulfonic acid has an amino group and a sulfonic acid group, and is an amphiphilic group surfactant, which can improve the wettability and contact between asphalt and graphite matrix; maleic anhydride grafted polyethylene wax has a maleic anhydride group, has both polar and non-polar groups / segments, and is an organic / inorganic compatibilizer and coupling agent, and the polyethylene wax matrix can provide good asphalt compatibility, and promote the better coupling effect of maleic anhydride groups; benzenesulfonic anhydride has a disulfonic acid group, and sulfobenzoic acid has both a sulfonic acid group and a carboxyl group, and the two can provide a tighter three-dimensional network structure during the asphalt melting process, reduce the gap between graphite and the carbonized layer, and thus can densify the carbonized layer.

[0021] As a specific embodiment of the above-mentioned asphalt solid phase composition for coating of the present invention, the coating asphalt is a high-temperature coating asphalt, and its softening point is 200-285°C, preferably 240-285°C; the coking value is ≥50%, preferably ≥60%;

[0022] The quinoline insoluble matter content in the coated asphalt is ≤0.3wt%, and the ash content is ≤0.1wt%, and both the quinoline insoluble matter content and the ash content are calculated based on the total weight of the coated asphalt as 100%;

[0023] The median particle size D50 of the coated asphalt is 1-8 μm, preferably 2-4 μm.

[0024] In the asphalt solid phase composition for coating provided by the present invention, each component is solid phase, and the modification aid therein achieves the effect of uniform dispersion and modification of asphalt through melting during the temperature-raising carbonization process and the dripping melting characteristics of the asphalt itself, thereby avoiding the use of various solvents, reducing processing costs and operating difficulties, and the amount of modification aid added is low, which has little effect on the residual carbon rate of the coating material. Compared with conventional processes, the material cost increase is small.

[0025] On the other hand, the present invention also provides a method for preparing a modified asphalt-coated natural graphite negative electrode material, wherein the preparation method comprises:

[0026] S1: Under the protection of inert gas, the natural graphite and the above-mentioned asphalt solid phase composition for coating are mixed uniformly to obtain a mixture;

[0027] S2: Under the protection of an inert gas, the mixture is carbonized to obtain the modified asphalt-coated natural graphite negative electrode material.

[0028] As a specific embodiment of the preparation method described above of the present invention, in S1, the natural graphite is spherical graphite, the median particle size D50 is 16-18 μm, the fixed carbon content is ≥99.95wt%, and the fixed carbon content is calculated based on the total weight of the spherical graphite as 100%;

[0029] The tap density of the spherical graphite is ≥0.96 g / cm 3 , preferably ≥0.98g / cm 3 ;

[0030] The specific surface area of ​​the spherical graphite is ≤6.5cm 2 / g, preferably ≤6.0cm 2 / g.

[0031] The natural graphite and coated asphalt used in the present invention can be purchased or obtained by conventional means in the art.

[0032] As a specific implementation of the above preparation method of the present invention, in S1, the powder temperature during the mixing process / the entire mixing process is ≤50°C.

[0033] As a specific implementation of the above-mentioned preparation method of the present invention, in S1, the mixing process is carried out in a mixer.

[0034] As a specific embodiment of the preparation method described above of the present invention, in S2, the carbonization includes heating the temperature to 1050-1350°C at a heating rate of 1-10°C / min and keeping the temperature for 1-6h.

[0035] As a specific embodiment of the preparation method described above of the present invention, in S2, the carbonization is carried out in an atmosphere furnace.

[0036] As a specific embodiment of the preparation method described above of the present invention, in S2, after carbonization, the obtained carbonization product is first naturally cooled, and then dispersed, screened and demagnetized to obtain the modified asphalt-coated natural graphite negative electrode material.

[0037] The method for preparing the modified asphalt-coated natural graphite negative electrode material provided by the present invention has a simple process, no complicated operation steps, and does not involve liquid phase treatment.

[0038] On the other hand, the present invention also provides a modified asphalt-coated natural graphite negative electrode material, wherein the modified asphalt-coated natural graphite negative electrode material is prepared by the preparation method of the modified asphalt-coated natural graphite negative electrode material described above, and includes natural graphite and an amorphous carbon coating layer coated on the surface of the natural graphite.

[0039] In the modified asphalt-coated natural graphite negative electrode material provided by the present invention, the function of the amorphous carbon coating layer is to repair the surface defects of natural graphite, reduce the specific surface area, isolate the electrolyte and the natural graphite body, and reduce the co-embedding phenomenon of lithium ions and electrolyte molecules, thereby significantly improving the electrochemical properties of the natural graphite negative electrode material, such as the first effect and long cycle performance.

[0040] On the other hand, the present invention further provides a lithium-ion battery, wherein the negative electrode of the lithium-ion battery comprises the modified asphalt-coated natural graphite negative electrode material described above.

[0041] Compared with the prior art, the beneficial technical effects that can be achieved by the present invention include:

[0042] The present invention adds a modification aid during the preparation of a modified asphalt-coated natural graphite negative electrode material, and the modification aid includes a saturated long-chain component, a low-molecular wax component and a component containing a modification group. The components in the modification aid complement each other and work synergistically to reduce the softening point and viscosity of the asphalt during the carbonization process, change the surface tension between the asphalt and the graphite, enhance the wettability of the asphalt to the graphite, allow the asphalt to penetrate into the pores inside the graphite particles, repair cracks on the graphite surface, and improve the uniformity and density of the amorphous carbon coating layer, thereby effectively improving the electrochemical properties of the negative electrode material, such as the first-cycle coulomb efficiency and long-cycle performance, and reducing the specific surface area and AC impedance of the negative electrode material.

[0043] The present invention can obtain a natural graphite negative electrode material product with better performance by compounding different modifying additives under the condition of low addition amount of coating material (coating asphalt + modifying additive), and the preparation process is simple and the product has high cost performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0045] Figure 1a and Figure 1b This is a scanning electron microscope image of the modified asphalt-coated natural graphite negative electrode material provided in Example 1 of the present invention.

[0046] Figure 1c and Figure 1d This is a scanning electron microscope image of the modified asphalt-coated natural graphite negative electrode material provided in Example 2 of the present invention.

[0047] Figure 1e and Figure 1fThis is a scanning electron microscope image of the modified asphalt-coated natural graphite negative electrode material provided in Example 3 of the present invention.

[0048] Figure 2 Infrared transmission spectra of the modified asphalt-coated natural graphite negative electrode materials provided in Examples 1 to 3 of the present invention.

[0049] Figure 3 This is a diagram of the softening process of the coating material (coated asphalt + modification aid) provided in Example 1 and Comparative Examples 1 to 3 of the present invention.

[0050] Figure 4 The wetting contact angle diagrams of the coating materials (coated asphalt + modification additive) provided in Example 1 and Comparative Examples 1 to 3 of the present invention.

[0051] Figure 5 The AC impedance spectra of the negative electrode materials provided in Examples 1 to 3 and Comparative Examples 1 to 7 of the present invention.

[0052] Figure 6 1C / 1C cycle diagram of the negative electrode materials provided for Examples 1 to 3 and Comparative Examples 1 to 7 of the present invention. DETAILED DESCRIPTION

[0053] It should be noted that the term "comprises" and any variations thereof in the specification and claims of the present invention and the above-mentioned drawings are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0054] "Scope" disclosed in the present invention is given in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges defined in this way are combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, for a specific parameter, a range of 60-120 and 80-110 is listed, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​listed are 1 and 2, and the maximum range values ​​listed are 3, 4 and 5, then the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.

[0055] In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in the present invention, and "0-5" is just an abbreviation of these numerical combinations.

[0056] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned in the present invention can be combined with each other to form a new technical solution.

[0057] In the present invention, unless otherwise specified, all technical features and preferred features mentioned in the present invention can be combined with each other to form a new technical solution.

[0058] In the present invention, unless otherwise specified, all steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0059] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the attached table, drawings and examples. The following described embodiments are some embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. Example 1

[0060] This embodiment provides a modified asphalt-coated natural graphite negative electrode material, which is prepared by a preparation method comprising the following specific steps:

[0061] S1: Natural graphite, coated asphalt and modified additives are mixed evenly in a mixer equipped with a cooling water interlayer, and high-purity nitrogen is introduced into the mixing process for protection. The temperature of the materials before mixing is measured by a laser temperature measuring gun to be 25.5°C, and the temperature after discharging is 26.4°C, to obtain a mixture;

[0062] The natural graphite is spherical graphite, which is a conventional commercial product with a median particle size of D50 = 16.71 μm, a fixed carbon content of 99.96 wt%, and a tap density of 0.98 g / cm 3 , with a specific surface area of ​​5.85cm 2 / g; the coated asphalt is also a conventional product on the market, with a measured softening point of 251°C, a coking value of 68.9%, a quinoline insoluble content of 0.17wt%, an ash content of 0.04wt%, and a median particle size D50 of 3.22μm;

[0063] The modified additives include stearic acid, BASF polyethylene wax and p-aminobenzenesulfonic acid, and the median particle sizes D50 are 7.22 μm, 8.98 μm and 8.16 μm respectively; the mass ratio of each raw material is spherical graphite: coated asphalt: stearic acid: BASF polyethylene wax: p-aminobenzenesulfonic acid = 1000:48:4.8:1.2:1.2;

[0064] S2: The above mixture is placed in an atmosphere furnace, and under the protection of high-purity nitrogen, the temperature is increased to 1150°C at a heating rate of 5°C / min, and the mixture is kept warm for 2 hours for carbonization. After the carbonization, the obtained product is naturally cooled, and then the product is dispersed, sieved, and demagnetized to obtain the modified asphalt-coated natural graphite negative electrode material. Example 2

[0065] This embodiment provides a modified asphalt-coated natural graphite negative electrode material, which is prepared by a preparation method comprising the following specific steps:

[0066] S1: Natural graphite, coated asphalt and modified additives are mixed evenly in a mixer equipped with a cooling water interlayer, and high-purity nitrogen is introduced into the mixing process for protection. The temperature of the materials before mixing is measured by a laser temperature measuring gun to be 25.0°C, and the temperature after discharging is 25.5°C, to obtain a mixture;

[0067] Wherein, the natural graphite is spherical graphite, and the spherical graphite and coated asphalt used are the same as those in Example 1; the modification additives include Sasobit, synthetic Fischer-Tropsch wax, maleic anhydride grafted polyethylene wax and benzenesulfonic anhydride, and the median particle sizes D50 are 8.50 μm, 6.99 μm, 5.30 μm and 8.14 μm, respectively; the mass ratio of each raw material is spherical graphite: coated asphalt: Sasobit: synthetic Fischer-Tropsch wax: maleic anhydride grafted polyethylene wax: benzenesulfonic anhydride = 1000:48:4.8:1.2:1.2:1.2;

[0068] S2: The above mixture is placed in an atmosphere furnace, and under the protection of high-purity nitrogen, the temperature is increased to 1150°C at a heating rate of 5°C / min, and the mixture is kept warm for 2 hours for carbonization. After the carbonization, the obtained product is naturally cooled, and then the product is dispersed, sieved, and demagnetized to obtain the modified asphalt-coated natural graphite negative electrode material. Example 3

[0069] This embodiment provides a modified asphalt-coated natural graphite negative electrode material, which is prepared by a preparation method comprising the following specific steps:

[0070] S1: Natural graphite, coated asphalt and modified additives are mixed evenly in a mixer equipped with a cooling water interlayer, and high-purity nitrogen is introduced into the mixing process for protection. The temperature of the materials before mixing is measured by a laser temperature measuring gun to be 23.0°C, and the temperature after discharging is 23.5°C, to obtain a mixture;

[0071] Wherein, the natural graphite is spherical graphite, and the spherical graphite and coated asphalt used are the same as those in Example 1; the modification additives include stearic acid, stearic acid amide, Honeywell wax powder, sulfobenzoic acid and maleic anhydride grafted polyethylene wax, and the median particle sizes D50 are 7.22 μm, 5.61 μm, 9.75 μm, 8.87 μm and 5.30 μm, respectively; the mass ratio of each raw material is spherical graphite: coated asphalt: stearic acid: stearic acid amide: Honeywell wax powder: sulfobenzoic acid: maleic anhydride grafted polyethylene wax = 1000:60:2.4:1.2:1.2:1.2:1.2;

[0072] S2: The above mixture is placed in an atmosphere furnace, and under the protection of high-purity nitrogen, the temperature is increased to 1300°C at a heating rate of 5°C / min, and the temperature is kept for 2 hours for carbonization. After the carbonization is completed, the obtained product is naturally cooled, and then dispersed, sieved, and demagnetized to obtain the modified asphalt-coated natural graphite negative electrode material.

[0073] Comparative Example 1

[0074] This comparative example provides a bitumen-coated natural graphite negative electrode material, which differs from Example 1 only in that no modification aid is added.

[0075] Comparative Example 2

[0076] This comparative example provides a modified asphalt-coated natural graphite negative electrode material, which differs from Example 1 only in that the modification aid is stearic acid, and the mass ratio of the raw materials is spherical graphite:coating asphalt:stearic acid=1000:48:7.2.

[0077] Comparative Example 3

[0078] This comparative example provides a modified asphalt-coated natural graphite negative electrode material, which differs from Example 1 only in that the modification aid is p-aminobenzenesulfonic acid, and the mass ratio of the raw materials is spherical graphite: coated asphalt: p-aminobenzenesulfonic acid = 1000:48:7.2.

[0079] Comparative Example 4

[0080] This comparative example provides a modified asphalt-coated natural graphite negative electrode material, which differs from Example 1 only in that:

[0081] The modification aids are stearic acid and p-aminobenzenesulfonic acid, and the mass ratio of the raw materials is spherical graphite: coated asphalt: stearic acid: p-aminobenzenesulfonic acid = 1000:48:4.8:2.4.

[0082] Comparative Example 5

[0083] This comparative example provides a modified asphalt-coated natural graphite negative electrode material, which differs from Example 1 only in that:

[0084] The modification aids are stearic acid and BASF polyethylene wax, and the mass ratio of the raw materials is spherical graphite: coated asphalt: stearic acid: BASF polyethylene wax = 1000:48:4.8:2.4.

[0085] Comparative Example 6

[0086] This comparative example provides a modified asphalt-coated natural graphite negative electrode material, which differs from Example 1 only in that:

[0087] The mass ratio of the raw materials is spherical graphite: coated asphalt: stearic acid: BASF polyethylene wax: p-aminobenzenesulfonic acid = 1000:48:4.8:6:1.2.

[0088] Comparative Example 7

[0089] This comparative example provides a modified asphalt-coated natural graphite negative electrode material, which differs from Example 1 only in that:

[0090] The mass ratio of the raw materials is spherical graphite: coated asphalt: stearic acid: BASF polyethylene wax: p-aminobenzenesulfonic acid = 1000:48:4.8:1.2:8.

[0091] Test Example 1

[0092] In this test example, ZEISS SUPRA55 was used to perform field emission scanning electron microscopy analysis on the modified asphalt-coated natural graphite negative electrode materials provided in Examples 1 to 3 of the present invention under conventional test conditions. The obtained scanning electron microscopy images are shown in FIG. Figure 1a-1f As shown. Among them, Figure 1a and Figure 1bThis is a scanning electron microscope image of the modified asphalt-coated natural graphite negative electrode material provided in Example 1 of the present invention. Figure 1c and Figure 1d This is a scanning electron microscope image of the modified asphalt-coated natural graphite negative electrode material provided in Example 2 of the present invention. Figure 1e and Figure 1f This is a scanning electron microscope image of the modified asphalt-coated natural graphite negative electrode material provided in Example 3 of the present invention.

[0093] from Figure 1a-1f It can be seen that the modified asphalt-coated natural graphite negative electrode material particles provided in Examples 1 to 3 of the present invention are potato-shaped and round, and an amorphous carbon coating layer can be observed on the surface and in the gaps between the graphite sheets.

[0094] Test Example 2

[0095] In this test example, Bruker INVENIO-R was used to perform infrared transmission spectroscopy analysis on the modified asphalt coated natural graphite negative electrode materials provided in Examples 1 to 3 of the present invention under conventional test conditions. The obtained infrared transmission spectra are shown in FIG. Figure 2 As shown. Figure 2 It can be seen that the modified asphalt-coated natural graphite negative electrode materials provided in Examples 1 to 3 of the present invention have no obvious characteristic peak signal in the fingerprint area, indicating that the modification additive has no residue after carbonization.

[0096] Test Example 3

[0097] In this test example, according to the coating material (coating asphalt + modification additive) ratio provided in Example 1 and Comparative Examples 1 to Comparative Examples 3, spherical graphite was used as the substrate, and the softening of the coating material and its infiltration of graphite were continuously recorded from room temperature to 500°C, at a heating rate of 5°C / min and in an inert atmosphere. The obtained softening process diagram and wetting contact angle diagram are shown respectively as follows: Figure 3 and Figure 4 shown.

[0098] from Figure 3 It can be seen that compared with the comparative example 1 without adding the modifying agent, the softening point temperature of the coated material in the comparative example 2 is reduced by about 40°C, indicating that the saturated long-chain components such as stearic acid as the modifying agent can reduce the softening point of the coated asphalt, so that the coated asphalt can enter the state of good infiltration with the spherical graphite more quickly. Figure 4 As shown, compared with Example 1 without adding a modifying agent, the wetting contact angle in the wetted state in Example 3 is significantly reduced from about 70° to 18°, and can still be maintained at 53° after continued heating and curing, indicating that components containing modifying groups such as p-aminobenzenesulfonic acid as modifying agents can greatly improve the wetting performance of the coated asphalt on the graphite group.

[0099] from Figure 3 and Figure 4 It can be seen that, compared with Comparative Examples 1 to 3, in Example 1 of the present invention, by compounding saturated long-chain components, low-molecular wax components and components containing modifying groups as modification aids, it is possible to achieve the effect of both lowering the softening point and improving the wettability of the coated asphalt, thereby extending the wetting time of the coated asphalt on the spherical graphite during the heating process, making it easier for the coated asphalt to penetrate into the pores inside the spherical graphite particles, and better repairing the cracks on the surface of the spherical graphite.

[0100] Test Example 4

[0101] In this test example, Bettersize2600 and Micromeritics TriStar II 3020 were used to test the particle size and specific surface area of ​​the negative electrode materials provided in each embodiment and the comparative example under conventional test conditions. CHI660E was also used to test the AC impedance spectrum of the negative electrode materials provided in each embodiment and the comparative example under conventional test conditions. The obtained AC impedance spectrum is shown in FIG. Figure 5 The obtained particle size and specific surface area data are shown in Table 1 below;

[0102] This test example also tests the electrochemical properties of the negative electrode materials provided in each embodiment and comparative example, including:

[0103] The natural graphite negative electrode material provided in each embodiment and each comparative example was used as the negative electrode active material, and the three were mixed evenly in a mass ratio of negative electrode active material: LA133: SuperP = 94:3:3, and then coated on a copper foil current collector, and then dried, cut, and rolled to obtain a negative electrode sheet for standby use.

[0104] The negative electrode sheets obtained above were assembled into 2032 button cells and tested for the first charge capacity and the first week coulombic efficiency, wherein the counter electrode was a lithium sheet, the solute of the electrolyte was LiPF6, the solvent was a mixture of DEC, DMC and EC in a volume ratio of 1:1:1, the concentration of the solute was 1 mol / L, the diaphragm was commercially available Celgard2320, and the test was carried out on a battery tester CT300A1U, the charge and discharge voltage was 0.005-1.5V, deep discharge (0.1C-0.01C) and 0.1C charge were carried out in the first week, and the first charge capacity and the first week coulombic efficiency obtained from the test are also listed in Table 1 below.

[0105] For the cycle performance of the negative electrode material, the charge and discharge were carried out at 1C / 1C conditions according to the mass ratio of active material: LA133:SuperP=90:5:5. The other test conditions were the same as the first charge capacity and first week coulomb efficiency test process. The obtained 1C / 1C cycle diagram is shown in the figure below. Figure 6 The 1C / 1C 500-cycle capacity retention results are also listed in Table 1 below.

[0106] Table 1 Comparison of the first week charging specific capacity, first efficiency, particle size and specific surface area of ​​the negative electrode materials provided by Examples 1 to 3 and Comparative Examples 1 to 7

[0107]

[0108] Note: The present invention tests the negative electrode material by making a button half-cell. Under normal circumstances, an improvement of 0.2%-0.3% in the first efficiency is considered to be effective, and an improvement of more than 0.4% in the first efficiency is considered to be significant. An improvement of 3%-5% in the 1C / 1C 500-week cycle capacity retention rate is considered to be effective, and an improvement of more than 5% in the 1C / 1C 500-week cycle capacity retention rate is considered to be significant.

[0109] From Table 1 and Figure 5-Figure 6 It can be seen that compared with the asphalt-coated natural graphite negative electrode material provided in Comparative Example 1, the specific surface area and AC impedance of the modified asphalt-coated natural graphite negative electrode material obtained in Comparative Example 2 after adding only stearic acid as a modification aid are significantly reduced, but the first efficiency is basically not improved, and the cycle performance is reduced, and the 1C / 1C 500-week cycle capacity retention rate decreases from 86.1% to 85.4%.

[0110] Compared with the asphalt-coated natural graphite negative electrode material provided in Comparative Example 1, the first efficiency of the modified asphalt-coated natural graphite negative electrode material obtained in Comparative Example 3 after adding only p-aminobenzenesulfonic acid as a modification aid was increased from 93.45% to 93.66%. Although the first efficiency was improved to a certain extent, the specific surface area and AC impedance were slightly decreased, but the cycle performance declined and the comprehensive performance could not meet the requirements.

[0111] Compared with the asphalt-coated natural graphite negative electrode material provided in Comparative Example 1, the modified asphalt-coated natural graphite negative electrode material obtained in Comparative Example 4 after adding only stearic acid and p-aminobenzenesulfonic acid as modification aids has a lower AC impedance and improved long cycle performance, and the specific surface area is also reduced to a certain extent, but the first efficiency is only increased by 0.15%, and the 1C / 1C 500-week cycle capacity retention rate is only increased by 0.6%. The improvement effect is not obvious enough.

[0112] Compared with the asphalt-coated natural graphite negative electrode material provided in Comparative Example 1, the specific surface area of ​​the modified asphalt-coated natural graphite negative electrode material obtained in Comparative Example 5 after adding only stearic acid and BASF polyethylene wax as modification aids is significantly reduced, but the initial efficiency is slightly reduced, and the overall performance cannot meet the requirements.

[0113] In Example 1 and Example 2 of the present invention, modified asphalt-coated natural graphite negative electrode materials are prepared by compounding modification additives under the same conditions as those of Comparative Examples 1 to 5, with the amount of coating asphalt and the sintering system being the same.

[0114] Compared with the negative electrode material provided in Comparative Example 1, the modified asphalt-coated natural graphite negative electrode materials provided in Examples 1 and 2 of the present invention exhibit balanced electrochemical performance and physical parameters. The first efficiency is increased by 0.44% and 0.58%, respectively, and the 1C / 1C 500-cycle capacity retention rate is increased by 5.6% and 4.1%, respectively. The improvement effects are quite obvious, and the specific surface area and AC impedance are significantly reduced.

[0115] Compared with the negative electrode material provided in Comparative Example 2, the modified asphalt-coated natural graphite negative electrode materials provided in Examples 1 and 2 of the present invention exhibit balanced electrochemical performance and physical parameters. The first efficiency is increased by 0.41% and 0.55%, respectively, and the 1C / 1C 500-cycle capacity retention rate is increased by 6.3% and 4.8%, respectively. The improvement effects are quite obvious, and the specific surface area and AC impedance are significantly reduced.

[0116] Compared with the negative electrode material provided in Comparative Example 3, the modified asphalt-coated natural graphite negative electrode materials provided in Examples 1 and 2 of the present invention exhibit balanced electrochemical performance and physical parameters. The first efficiency is increased by 0.23% and 0.37%, respectively, and the 1C / 1C 500-cycle capacity retention rate is increased by 7.0% and 5.5%, respectively. The improvement effects are quite obvious, and the specific surface area and AC impedance are significantly reduced.

[0117] Compared with the negative electrode material provided in Comparative Example 4, the modified asphalt-coated natural graphite negative electrode materials provided in Examples 1 and 2 of the present invention exhibit balanced electrochemical performance and physical parameters. The first efficiency is increased by 0.29% and 0.43%, respectively, and the 1C / 1C 500-cycle capacity retention rate is increased by 5.0% and 3.5%, respectively. The improvement effects are quite obvious, and the specific surface area and AC impedance are significantly reduced.

[0118] Compared with the negative electrode material provided in Comparative Example 5, the modified asphalt-coated natural graphite negative electrode materials provided in Examples 1 and 2 of the present invention exhibit balanced electrochemical performance and physical parameters. The first efficiency is increased by 0.48% and 0.62%, respectively, and the 1C / 1C 500-cycle capacity retention rate is increased by 4.7% and 3.2%, respectively. The improvement effects are quite obvious, and the specific surface area and AC impedance are both reduced.

[0119] Compared with Example 1, Comparative Example 6 increases the amount of low molecular weight wax component. Figure 5-Figure 6 The test results shown indicate that, compared with the modified asphalt-coated natural graphite negative electrode material provided in Example 1, the various performances of the negative electrode material provided in Comparative Example 6 are significantly reduced. Specifically, the first efficiency is reduced by 0.80%, and the 1C / 1C 500-cycle capacity retention rate is reduced by 9.9%. This indicates that excessive low-molecular wax components seriously affect the performance improvement effect of the modification additive on the negative electrode material.

[0120] Compared with Example 1, Comparative Example 7 increases the amount of the component containing the modified group. Figure 5-Figure 6 The test results shown show that compared with the modified asphalt-coated natural graphite negative electrode material provided in Example 1, the various performances of the negative electrode material provided in Comparative Example 7 are significantly reduced. Specifically, the first efficiency is reduced by 0.51%, the 1C / 1C 500-cycle capacity retention rate is reduced by 7.3%, and the AC impedance, specific surface area, etc. have not achieved good improvement effects, which indicates that too many components containing modified groups are not conducive to improving the performance of the negative electrode material.

[0121] Combined with the above Figure 3 and Figure 4 The softening and wetting results of the coating material shown are sufficient to prove that the components in the composite modification additive used in the present invention complement each other and act synergistically, thereby achieving the effect of improving the electrochemical performance and physical parameters of the negative electrode material by lowering the softening point of the coating asphalt and improving the wettability of the coating asphalt.

[0122] In Example 3 of the present invention, by increasing the amount of coating asphalt and the carbonization temperature, and further adapting the modification additive according to the preparation conditions, a negative electrode material product with better first effect and cycle performance, lower impedance and specific surface area is obtained. This proves that the present invention can produce natural graphite negative electrode materials with different properties, and negative electrode products with different properties and production costs can be selected according to customer customization needs.

[0123] The above is only a specific embodiment of the present invention, and cannot be used to limit the scope of the invention. Therefore, the replacement of equivalent components, or equivalent changes and modifications made according to the protection scope of the present invention should still fall within the scope of the present invention. In addition, the technical features in the present invention can be freely combined with each other, with each other and with each other, and with each other.

Claims

1. A coating asphalt solid phase composition for forming an amorphous carbon coating layer coated on the surface of natural graphite, characterized in that: The coating asphalt solid phase composition comprises coating asphalt and a modification agent, wherein the mass ratio of natural graphite, coating asphalt and modification agent is 1000:45-80:3-12; the modification agent comprises a saturated long chain component, a low molecular wax component and a component containing a modification group in a mass ratio of 2-10:0.5-5:0.5-7; Wherein, the saturated long-chain component includes one or a combination of stearic acid, stearic acid amide and Sasobit; The molecular weight of the low molecular wax component is in the range of 100-5000, and the low molecular wax component includes one or a combination of synthetic Fischer-Tropsch wax, polyethylene wax and Honeywell wax powder; The component containing the modified group includes one or a combination of p-aminobenzenesulfonic acid, maleic anhydride grafted polyethylene wax, benzenesulfonic anhydride and sulfobenzoic acid.

2. The asphalt solid phase composition for coating according to claim 1, characterized in that: The modification aid is in the form of powder, and the median particle size D50 is 3-20 μm.

3. The asphalt solid phase composition for coating according to claim 1 or 2, characterized in that: The softening point of the coated asphalt is 200-285°C, and the coking value is ≥50%; The quinoline insoluble matter content in the coated asphalt is ≤0.3wt%, and the ash content is ≤0.1wt%; The median particle size D50 of the coated asphalt is 1-8 μm.

4. A method for preparing a modified asphalt-coated natural graphite negative electrode material, characterized in that: The preparation method comprises: S1: Under the protection of inert gas, mixing natural graphite and the asphalt solid phase composition for coating according to any one of claims 1 to 3 to obtain a mixture; S2: Under the protection of an inert gas, the mixture is carbonized to obtain the modified asphalt-coated natural graphite negative electrode material.

5. The preparation method according to claim 4, characterized in that: In S1, the natural graphite is spherical graphite, the median particle size D50 is 16-18 μm, and the fixed carbon content is ≥99.95wt%; The tap density of the spherical graphite is ≥0.96 g / cm 3 ; The specific surface area of ​​the spherical graphite is ≤6.5cm 2 / g.

6. The preparation method according to claim 4 or 5, characterized in that: In S1, the powder temperature during the mixing process is ≤50°C.

7. The preparation method according to claim 4 or 5, characterized in that: In S2, the carbonization includes heating the temperature to 1050-1350°C at a heating rate of 1-10°C / min and keeping the temperature for 1-6h.

8. A modified asphalt coated natural graphite negative electrode material, characterized in that: The modified asphalt coated natural graphite negative electrode material is prepared by the preparation method of the modified asphalt coated natural graphite negative electrode material according to any one of claims 4 to 7, and comprises natural graphite and an amorphous carbon coating layer coated on the surface of the natural graphite.

9. A lithium ion battery, characterized in that: The negative electrode of the lithium-ion battery comprises the modified asphalt-coated natural graphite negative electrode material according to claim 8.

Citation Information

Patent Citations

  • Preparation method and system of petroleum-based coated asphalt with low quinoline insolubles and high softening point

    CN115093874A

  • Coating agent, anode material, lithium ion battery and preparation method thereof

    CN106469814A

  • Preparation method of high-softening-point coated asphalt for lithium ion battery negative electrode material

    CN114437557A

  • Artificial graphite negative electrode material and preparation and application thereof

    CN119133406A

  • Method for producing negative electrode material for lithium ion secondary battery

    JP2013254728A